Online Review: Indikator Penilaian Kredibilitas Online dalam Platform E-commerce - Agustina, Lidya; Fayardi, Alifia Oktrina; Irwansyah, Irwansyah (Jurnal ILMU KOMUNIKASI, 2018)
Online credibility, either for a company or a merchant, is an important thing that have to be considered in the era of e-commerce development. Online review and online rating are part of indicators that used to represent merchant or seller’s online credibility in e-commerce platform. The existence of online review and online rating in e-commerce platform may affect the prominence and interpretation aspects which is associated with online credibility. This is a conceptual paper which aims to describe the concept of online review and its relation with online credibility.